New horizons in mobile and wireless communications. - Prasad, Ramjee; Mihovska, Albena (Artech House mobile communications series., 2009)
Based on cutting-edge research projects in the field, this book (part of a comprehensive 4-volume series) provides the latest details and covers the most impactful aspects of mobile, wireless, and broadband communications development. These books present key systems and enabling technologies in a clear and accessible manner, offering you a detailed roadmap the future evolution of next generation communications. Other volumes cover Radio Interfaces; Networks, Services and Applications; and Reconfigurability.